Transformasi Pembelajaran: Kontribusi Penelitian Tindakan Kelas bagi Guru - Ihsan Rizali; Rayi Siti Fitriani; Gemi Gustiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Introduction: Teachers face challenges in adapting innovative teaching methods in the digital era. Classroom Action Research (CAR) has emerged as a solution to enhance the quality of teaching and teacher competence. Objectives: To improve the quality of teaching and student learning outcomes, as well as to equip teachers with reflective and problem-solving skills. Methods: This study examines the development and trends of CAR research from 2018 to 2024 through a literature review. Findings: CAR has been proven effective in driving teaching transformation, enhancing teacher collaboration, and improving understanding of student needs. Conclusion: CAR serves as an effective instrument for teacher professional development. Its success depends on institutional support, teacher collaboration, and a commitment to reflection and continuous improvement.